2021
DOI: 10.1093/bjs/znab202.047
|View full text |Cite
|
Sign up to set email alerts
|

Damage-control surgery in patients with non-traumatic abdominal emergencies: A meta-analysis

Abstract: Objective After the successful implementation in trauma patients, damage control surgery (DCS) is being increasingly used in non-traumatic abdominal emergencies, too. However, non-trauma DCS (NT-DCS) is currently a matter of debate and has not yet been comprehensively assessed. The aim of this meta-analysis was to investigate the effect of NT-DCS on mortality in patients with abdominal emergencies. Methods Systematic literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A recent systemic review and meta-analysis of this topic identified 21 studies, only eight of which were comparative [3]. There were no randomised controlled trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systemic review and meta-analysis of this topic identified 21 studies, only eight of which were comparative [3]. There were no randomised controlled trials.…”
Section: Discussionmentioning
confidence: 99%
“…An international consensus paper proposed indications for the use of open abdomen in non-trauma surgery which included: decompressive laparotomy for compartment syndrome, management of peritonitis, vascular emergencies and severe acute pancreatitis not responsive to step-up conservative management [2]. The studies examining the role for laparostomy in non-trauma emergency in general, aside from the previous mentioned conditions, have not shown a clear benefit for laparostomy over conventional laparotomy [3]. There are currently no randomised controlled trials of this treatment, and non-randomised comparative studies have struggled to match like-for-like patients or to adjust for the many potentially confounding variables between treatment groups [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%